(untitled) (Revista de Ensino em Artes, Moda e Design, 2023)
In this article, I investigate the relationship between school uniforms and fashion in Minas Gerais during the Belle Époque period (1890-1914) (FOGG, 2014, p. 196). This relationship can be identified in several vehicles of memory of the material culture of school life in Minas Gerais: in the narrative of a normalist student from Diamantina (1893-1895), in the uniform project of the Normal School of Juiz de Fora (1896) and, finally, in the photographic artifacts of Colégio Nossa Senhora das Dores (CNSD) in Uberaba (1908-1912), a female Catholic confessional school in the final period of the Belle Époque in the Triângulo Mineiro. The study is based on a reading of textual and iconographic documents with the objective of understanding the materialization of fashion content and its meanings that, through the coastal ports, entered the country, spreading through Minas, until reaching the Triângulo Mineiro, and that involved the school uniforms. I base the research on the investigation of fashion periodicals; in the narrative of a normalist from Minas Gerais; in a design of uniforms from that period and in photographs of CNSD graduating students; seeking to understand the concepts of fashion in the memory of school life. As a theoretical-methodological procedure, I start from the intersection of text and images with several other sources in a dialectical perspective that situates the concept of fashion, the historical context and the resources of material culture, allowing to understand the production of culture and memory in secular and confessional schools from Minas Gerais, questions that go through the absorption of French fashion in the Brazilian Belle Époque.